1996
DOI: 10.1007/bf02306083
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of primary tumor regression with chemotherapy: Implications for the timing of surgery

Abstract: Rapid initial reduction in primary tumor volume with chemotherapy was observed in rhabdomyosarcoma, neuroblastoma, and hepatoblastoma. These data suggest that second-look resection may be feasible after two to three cycles of chemotherapy. This hypothesis may be tested by randomizing the timing of second-look surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Medary et al reported the kinetics of primary embryonal tumor regression in 24 children having rhabdomyosarcoma (n=16), neuroblastoma (n=5), or hepatoblastoma (n=3) (10). These authors measured tumor volume decay over time and initial cell counts, but did not include sAFP kinetics as a measure of hepatoblastoma response to induction therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medary et al reported the kinetics of primary embryonal tumor regression in 24 children having rhabdomyosarcoma (n=16), neuroblastoma (n=5), or hepatoblastoma (n=3) (10). These authors measured tumor volume decay over time and initial cell counts, but did not include sAFP kinetics as a measure of hepatoblastoma response to induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Medary et al reported that in three cases of hepatoblastoma, a rapid initial reduction in primary tumor volume could be observed and that a plateau in any further tumor decay appeared after cycle two (treatment according to Children's Cancer Group, CCG-8881) (10). These authors suggested that post-induction complete resection of hepatoblastoma could be accomplished after chemotherapy cycle two or three.…”
mentioning
confidence: 99%
“…Most children undergo delayed surgery after the completion of the fifth cycle of induction chemotherapy, even though tumor volume reduction plateaus after the second or third cycle of chemotherapy. 39 Other groups are performing surgery as soon as locoregional disease appears, radiographically, to be resectable. 40 Although initial surgical resection is not often appropriate for patients with neuroblastoma, the principle of resection at the earliest feasible time should be considered.…”
Section: Risk and Treatment Stratificationmentioning
confidence: 99%
“…Historically, surgical resection was attempted after four cycles of chemotherapy, and further chemotherapy was planned if the tumour was unresectable after four cycles. There is evidence to suggest that the radiographic response of the tumour to chemotherapy plateaus after two cycles and tumour cells may acquire resistance with increasing number of cycles of chemotherapy. The current consensus is to attempt earlier resection if tumours are amenable to surgical management after two cycles of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%